2020
DOI: 10.1111/sdi.12864
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of hemodialysis and hemodiafiltration on left ventricular hypertrophy in end‐stage renal disease patients: A systematic review and meta‐analysis

Abstract: Whether hemodiafiltration (HDF) is better than conventional hemodialysis (HD) in improving left ventricular hypertrophy (LVH), defined as reduction of the left ventricular mass index (LVMi) and increasing the ejection fraction (EF), is unclear. A systematic literature search was performed. Primary outcome was the mean difference between pre‐ and post‐procedural LVMi. Secondary outcome was the mean difference in EF. Seven studies with a total of 845 patients were included. The pooled mean difference between pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…In a meta-analysis comparing cardiac outcomes of HD and HDF, in terms of LVM and ejection fraction, a similar improvement of left ventricular hypertrophy was found in patients receiving HD or OL-HDF. 30 Similarly, in a study comparing HD and OL-HDF, vascular stiffness, as assessed by pulse wave velocity, was not affected by dialysis modality. 31…”
Section: Arterial Stiffness and Pwvmentioning
confidence: 92%
“…In a meta-analysis comparing cardiac outcomes of HD and HDF, in terms of LVM and ejection fraction, a similar improvement of left ventricular hypertrophy was found in patients receiving HD or OL-HDF. 30 Similarly, in a study comparing HD and OL-HDF, vascular stiffness, as assessed by pulse wave velocity, was not affected by dialysis modality. 31…”
Section: Arterial Stiffness and Pwvmentioning
confidence: 92%
“…Recently, Páll et al [36] reported that T peak-end interval was lower under HDF than under HD and showed a significant correlation with LVMI. However, in a recently released meta-analysis, conventional HD and HDF showed no significant variations in the impact on the changes of LVMI and ejection fraction [37]. Hence, additional studies will be required to demonstrate whether HDF helps improve left ventricular hypertrophy to enhance survival.…”
Section: Vascular Stiffnessmentioning
confidence: 98%
“…Although some studies suggest that endothelial function and arterial stiffness improve with the use of HDF [ 91 ], so far, it has not demonstrated a positive impact over HD in the alterations of intratherapeutic cardiac motility [ 92 ], in arterial stiffness evaluated by pulse wave velocity [ 93 ], or in the improvement in left ventricular mass and ejection fraction [ 94 ].…”
Section: Impact Of Hemodiafiltration On Clinical Outcomesmentioning
confidence: 99%